Endometriosis: an enigmatic disease with many faces - Limbachiya, Dipak J.; Agrawal, Grishma P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Endometriosis is a benign disease defined by the presence of the endometrial glands and stroma outside of the uterus, both at pelvic and extra pelvic sites. We are reporting 4 unusual cases of endometriosis that are unique on their own due to site of endometriosis, presenting symptoms, complications and treatment. Endometriosis was present at post caesarean scar site in one case, at vault site in another case, in bladder in third case and in the last case it caused frozen pelvis with hydroureter, hydronephrosis and possibly infertility. All four patients have been treated laparoscopically and have been following up with no recurrence of its symptoms. The purpose of this article is to create awareness among Doctors about endometriosis, which is more common than previously thought as. Endometriosis has been rightly summed up in the phrase “The clock is definitely ticking, as we know millions of women still live lives awash in anguish, just as they did thousands of years ago and just as they will centuries from now unless we steer ourselves faster toward the long-elusive cure. Four thousand years is long enough; the time has come to end the empire of endometriosis”.